De la necesidad a la preferencias: los significados de la libertad - Iguíñiz Echeverría, Javier (2003)
In this paper we analyze the meaning of four concepts, subsistence, needs, wants and preferencesfrom the viewpoint of their association with the concepts of life sustenance and freedom. Ouraim is to show that the concentration by mainstream economic theory in the last two allows it toavoid dealing with the most important economic problems of today: poverty andunderdevelopment. Moreover, it trivializes the meaning of freedom, and specifically of freedomto choose. As freedom increases, loses substance.